2007
DOI: 10.1021/jo070114u
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Heterocyclic Privileged Medicinal Scaffolds by a Multicomponent Reaction of Malononitrile with Aldehydes and Thiols

Abstract: Heterocyclic privileged medicinal scaffolds involving pyridine, 1,4-dihydropyridine, chromeno[2,3-b]pyridine, and dihydro-1,4-dithiepine frameworks are prepared via a single-step multicomponent reaction of structurally diverse aldehydes with various thiols and malononitrile. Mechanistic studies of the synthetic pathway leading to pyridines reveal that 1,4-dihydropyridines undergo oxidation by the intermediate Knoevenagel adducts rather than by air oxygen. The use of o,o'-disubstituted aromatic aldehydes leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(102 citation statements)
references
References 24 publications
6
85
0
1
Order By: Relevance
“…The products are accomplished in good to excellent yields and their physical and spectral data are in agreement with literature reports. 12,14,21 Indeed, the method has the ability to tolerate functional groups such as methoxy, nitro, halides, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The products are accomplished in good to excellent yields and their physical and spectral data are in agreement with literature reports. 12,14,21 Indeed, the method has the ability to tolerate functional groups such as methoxy, nitro, halides, etc.…”
Section: Resultsmentioning
confidence: 99%
“…11 In view of their high significance, many methodologies have been developed for the construction of the pyridine skeleton. Various basic catalysts like piperidine, Et 12 and TBAH (tetrabutylammonium hydroxide) 12 have also been used for this reaction. Sridhar et al 13 showed that this reaction can be carried out using Lewis acid catalyst (ZnCl 2 ), which shows better results than base catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this condensation has been carried out under basic conditions using various bases such as, Et 3 N, DABCO, piperidine 10 , morpholine, thiomorpholine, pyrrolidine, N,N-DIPEA, pyridine, 2,4,6-collidine, DMAP, aniline, Nmethylaniline, N,N-dimethylaniline and N,N-diethylaniline 10 13 . However, most of these methods suffer by the formation of inevitable side products, which results in lower yield of desired product with long reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…MCRs comply with the principles of green chemistry in terms of economy of steps as well as many of the rigid criteria of an ideal organic synthesis. These reactions are effective in construction highly functionalized small organic molecules from readily available starting materials in a single step with natural flexibility for creating molecular complexity and diversity coupled with minimization of time, labor, cost and waste production [3][4][5][6] . The pyran nucleus is a fertile source of biologically important molecules.…”
Section: Introductionmentioning
confidence: 99%